THE ROLE OF ARTIFICIAL INTELLIGENCE IN CRIMINAL LITIGATION IN INTERNATIONAL LAW:THE INFLUENCE OF THE PRINCIPLE OF PARTY AUTONOMY ON THE COURT’S ADAPTATION TO INTERNATIONAL TREATIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The principle of party autonomy has had a dual impact on the court's adaptation to international treaties.On the one hand, this principle has prompted the court to pay more attention to the agreement arrangements of the parties and improve the flexibility of the application of international treaties; on the other hand, excessive emphasis on the autonomy of the parties may weaken the effect of the unified application of international treaties.